Monitoring/Evaluation in Nutritional Therapy for People with Gastrointestinal Complaints: Online Survey with Dietitians - Zbären, Eveline; Padmanabhan, Srividhya; Jent, Sandra (Aktuelle Ernährungsmedizin, 2022)
Introduction Dietary interventions are part of the therapy approach in gastrointestinal disorders. However, guidance on what outcomes to assess (in the form of a core outcome set) for dietitians to demonstrate the effectiveness of their interventions is lacking. This study provides preliminary work for the development of a core outcome set to systematically assess outcomes of nutrition therapy in clients with gastrointestinal complaints by examining how monitoring/evaluation are conducted by dietitians.Methods This is a quantitative online survey for dietitians to assess the current situation around the globe concerning monitoring and evaluation. An online survey with 26 questions divided into six sections (rated importance, implementation, resources/obstacles, instrument requirements, statistical questions and experiences with the Nutrition Care Process) was developed. The questionnaire was available in English, French and German.Results In total 740 responses were analysed. Monitoring/evaluation of clients with gastrointestinal symptoms was rated by 98% to be quite important to very important. The systematic implementation of monitoring and evaluation according to a concept/model was rated by 57% as 'rather often' to 'very often/always'.Conclusion Dietitians are aware of the importance of the measurability of dietetic interventions. The most dominant barriers are lacking time in daily practice and lack of a suitable monitoring/evaluation instrument. A suitable core outcome set in the field of gastrointestinal complaints is needed to increase systematic monitoring/evaluation.Einleitung Diätetische Interventionen sind Teil des Therapieansatzes bei gastrointestinalen Beschwerden. Es fehlt jedoch eine Anleitung für Ernährungsberater*innen welche Ergebnisse/Outcomes (in Form eines Core Outcome Sets) zu bewerten sind, damit die Wirksamkeit ihrer ernährungstherapeutischen Interventionen nachweisbar sind. Diese Studie stellt die Vorarbeit für die Entwicklung eines Core Outcome Sets dar, zur systematischen Erfassung von ernährungstherapeutischen Outcomes bei Klienten mit gastrointestinalen Beschwerden. Die Durchführung von Monitoring/Evaluation durch die Ernährungsberater*innen wird untersucht.Methoden Es handelt sich um eine quantitative, weltweit durchgeführte Online-Erhebung unter Ernährungsberater*innen, zur Bewertung der aktuellen Situation in Bezug auf Monitoring und Evaluation. Es wurde ein Online-Erhebung mit 26 Fragen entwickelt, unterteilt in sechs Bereiche (bewertete Wichtigkeit, Durchführung, Ressourcen/Hindernisse, Anforderungen an ein Instrument, statistische Fragen und Nutrition Care Process Erfahrungen). Der Fragebogen stand in Englisch, Französich und Deutsch zur Verfügung.Ergebnisse Insgesamt wurden 740 Antworten ausgewertet. Monitoring/Evaluation in der Beratung von Klienten mit gastrointestinalen Symptomen wurde von 98% als ziemlich wichtig bis sehr wichtig eingestuft. Die systematische Durchführung von Monitoring und Evaluation anhand Konzepten/Modellen wurde von 57% als 'eher oft' bis 'sehr oft/immer' bewertet.Schlussfolgerung Ernährungsberater*innen sind sich der Wichtigkeit der Messbarkeit von diätetischen Interventionen bewusst. Die größten Hindernisse ist der Zeitmangel in der täglichen Praxis und das Fehlen eines geeigneten Instruments zur Durchführung von Monitoring/Evaluation. Um das systematische Monitoring/Evaluation zu fördern, wird ein geeignetes Core Outcome Set im Bereich der gastrointestinalen Beschwerden benötigt.
Keywords: outcome; gastrointestinal; dietitian; monitoring; evaluation